(untitled) (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2025)
Considering the problems associated with the consumption of organic foods that are manifesting among Ecuadorian consumers. This study aims to analyze and understand the purchase intention of organic food products among the centennial generation in Ecuador, identifying the antecedent variables that directly influence the purchase decision, thus providing a detailed understanding of the factors that affect the choice of products. organic by this specific generation in the Ecuadorian context. The research mainly adopts a quantitative approach with an exploratory scope. A sample of 376 Ecuadorian centennials was selected using a non-probabilistic method of homogeneous convenience. The tool used was a survey consisting of five descriptive questions and 19 items evaluated using a Likert scale of values from 1 to 5 points. For data analysis, the SEM-PLS technique was chosen, considered appropriate for exploratory research. And it was possible to determine variables that directly influence the real purchase (CR). Showing that while food safety awareness (CA) directly influences the actual purchase (CR), the emotional value (EV) and the social value (SV) need the intermediation of the purchase intention (IC) to drive the actual purchase. of organic food products.